Improved Method for Recovery of mRNA from Aquatic Samples and Its Application to Detection of mer Expression - Jeffrey, Wade H. (1994)
Previously described methods for extraction of mRNA from environmental samples may preclude detecting transcripts from genes that were present in low abundance in aquatic bacterial communities. By combining a boiling sodium dodecyl sulfate-diethylpyrocarbonate lysis step with acid-guanidinium extraction, we improved recovery of target mRNA from both pure cultures and environmental samples. The most significant advantage of the new protocol is that it is easily adapted to yield high recovery of mRNA from 142-mm-diameter flat filters and high-capacity cartridge filters. The lysis and extraction procedures are more rapid than previously described methods, and many samples can be handled at once. RNA extracts have been shown to be free of contaminating DNA. The lysis procedure does not damage target mRNA sequences, and mRNA can be detected from fewer than 10(6) bacterial cells. We used the new method to examine transcripts of genes responsible for detoxification of mercurial compounds. Induction of merA (specifying mercuric reductase) transcripts in stationary-phase Pseudomonas aeruginosa containing Tn501 occurred within 60 s of HgCl(2) addition and was proportional to the amount of Hg(II) added. The new technique also allowed the detection of merA transcripts from the microbial community of a mercury-contaminated pond (Reality Lake, Oak Ridge, Tenn.). Significant differences in merA transcript abundance were observed between different locations associated with the lake. The results indicate that the new method is simple and rapid and can be applied to the study of mer gene expression of aquatic communities in their natural habitats.